Silicon-based negative electrode material and preparation method thereof, silicon-based negative electrode pole piece and lithium ion battery

By alloying to prepare silicon-aluminum alloy and forming an aluminum fluoride layer on its surface, the problems of pulverization and low conductivity of silicon-based negative electrode materials are solved, high conductivity and excellent cycle performance are achieved, and the electrochemical performance of lithium-ion batteries is improved.

CN120767302APending Publication Date: 2025-10-10XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510828786.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode materials for lithium-ion batteries are prone to pulverization and cracking, and have low electrical conductivity, resulting in reduced electrochemical performance.

Method used

Silicon-aluminum alloy powder is prepared by alloying nano-silicon powder with nano-aluminum powder, and an aluminum fluoride layer is formed on the surface of the powder to improve the electrical conductivity and inhibit volume expansion.

Benefits of technology

It improves the ductility and conductivity of silicon-based negative electrode materials, reduces pulverization and cracking, enhances cycle performance and rate performance, and improves the utilization rate of active materials and the charge and discharge performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767302A_ABST
    Figure CN120767302A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, and discloses a silicon-based negative electrode material and a preparation method thereof, a silicon-based negative electrode plate and a lithium ion battery. The silicon-based negative electrode material comprises a silicon-aluminum alloy matrix and an aluminum fluoride layer coating the silicon-aluminum alloy matrix, the silicon-based negative electrode material is prepared by alloying nano silicon powder and nano aluminum powder to obtain silicon-aluminum alloy powder, then fluorinating the silicon-aluminum alloy powder, and forming an aluminum fluoride layer on the surface of the silicon-aluminum alloy powder. The silicon-aluminum alloy is prepared through ball milling, then the silicon-aluminum alloy is subjected to fluorination treatment, a layer of compact aluminum fluoride film is formed on the surface of the silicon-aluminum alloy, the silicon-based negative electrode material is obtained, and the silicon-based negative electrode material is high in conductivity, not prone to pulverization and excellent in cycle performance and rate capability. The lithium ion battery applying the silicon-based negative electrode material still has the capacity of 827mAh g <-1 > and keeps the coulombic efficiency of about 100% after 200 cycles under the current density of 500mAg <-1 >; under the current density of 2000mAg <-1 >, the capacity is greater than 1000mAh g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a silicon-based negative electrode material and a preparation method thereof, a silicon-based negative electrode plate, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries dominate the energy storage field due to their high theoretical energy density and have been commercialized in portable electronics and electric vehicles.

[0003] While significant breakthroughs have been made in the research of positive electrode materials for lithium-ion batteries, their negative electrode materials are still primarily based on commercial graphite. Commercial lithium-ion batteries, based on the intercalation / deintercalation reactions between graphite anodes and transition metal oxide cathodes, are already approaching their energy density limits. Furthermore, the higher specific capacity of currently developed ternary positive electrode materials requires more graphite to match, resulting in larger batteries and lower energy density.

[0004] Alloy anodes are based on alloying / de-alloying reactions and exhibit very high specific capacity during charge / discharge reactions, with the advantages of high energy density and high conductivity. Among them, the theoretical capacity of silicon-based alloy negative electrodes and phosphorus-based alloy negative electrodes are 4400mAh·g -1 and 2596mAh·g -1 , which is much higher than the graphite negative electrode currently used in lithium-ion batteries. However, silicon-based negative electrode materials produce a huge volume effect (~400%) during the charge and discharge process, causing the active material to pulverize and crack and fall off from the current collector, resulting in a sharp decline in capacity; in addition, the intrinsic conductivity of silicon is low (6.7×10 -4 S cm -1 ) results in poor conductivity of the negative electrode material, which in turn leads to poor high current discharge performance.

[0005] There is an urgent need to develop new silicon-based anode materials with high capacity and high electrochemical performance. Summary of the Invention

[0006] The present application provides a silicon-based negative electrode material and a preparation method thereof, a silicon-based negative electrode plate and a lithium-ion battery, aiming to solve the problem that the existing silicon-based negative electrode material of lithium-ion batteries is prone to pulverization and cracking, and has low conductivity, resulting in reduced electrochemical performance of lithium batteries.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions.

[0008] In a first aspect of the present application, a silicon-based negative electrode material is provided, comprising a silicon-aluminum alloy substrate and an aluminum fluoride layer coating the silicon-aluminum alloy substrate;

[0009] The silicon-based negative electrode material is prepared by alloying nano-silicon powder and nano-aluminum powder to obtain silicon-aluminum alloy powder, and then performing a fluorination treatment on the silicon-aluminum alloy powder to form an aluminum fluoride layer on the surface.

[0010] The second aspect of the present application provides a method for preparing the above-mentioned silicon-based negative electrode material, comprising:

[0011] S1, taking nano-silicon powder and nano-aluminum powder and mixing them evenly, and ball milling them in a ball mill under vacuum to obtain a precursor powder;

[0012] S2, the precursor powder is vacuum dried, then heat treated in an inert atmosphere, and cooled to obtain silicon-aluminum alloy powder;

[0013] S3, adding the silicon-aluminum alloy powder into a reaction furnace, introducing nitrogen trifluoride gas at 200-280° C. to react, thereby obtaining a silicon-based negative electrode material.

[0014] Preferably, the ball milling is wet ball milling, and the ball milling medium is anhydrous ethanol.

[0015] Further preferably, the ball-to-material ratio of the ball mill is 30:1, the rotation speed is 400-600 r / min, and the time is 15-20 h.

[0016] More preferably, the vacuum degree in the ball mill is ≤100 Pa.

[0017] Preferably, the heat treatment is specifically: heating to 650-750° C. in an inert atmosphere and keeping the temperature for 2-3 hours.

[0018] Preferably, in step S3, the flow rate of nitrogen trifluoride gas is 40-60 mL / min, and the reaction time is 1-5 min.

[0019] Preferably, the mass ratio of the nano-silicon powder to the nano-aluminum powder is (1-2):1.

[0020] In a third aspect of the present application, a silicon-based negative electrode plate is provided, which includes the above-mentioned silicon-based negative electrode material.

[0021] In a fourth aspect of the present application, a lithium-ion battery is provided, wherein the negative electrode thereof is the above-mentioned silicon-based negative electrode sheet.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] This application prepares silicon-aluminum alloy by ball milling, and then fluorinates the silicon-aluminum alloy to form a dense aluminum fluoride film on its surface to obtain a silicon-based negative electrode material. The material has high electrical conductivity, is not easy to pulverize, and has excellent cycle performance and rate performance. On the one hand, by doping aluminum to prepare silicon-aluminum alloy, the ductility and electrical conductivity of the silicon-based negative electrode material are improved, and the probability of its pulverization and cracking is greatly reduced; on the other hand, the aluminum fluoride coating formed by the fluorination treatment can not only inhibit the volume expansion of silicon nanoparticles in the silicon-based negative electrode material during the lithium storage process, further reduce pulverization and cracking, and improve the utilization rate of active substances; and aluminum fluoride reacts with the electrolyte to induce the formation of lithium fluoride, the main substance in the solid electrolyte membrane, and play the role of regulating the solid electrolyte membrane, effectively solving the performance degradation problem caused by the fragmentation and reconstruction of the solid electrolyte membrane during the battery charging and discharging process.

[0024] The lithium-ion battery using the silicon-based negative electrode material of the present application has a high -1 The current density of 1.577 mAh g was still maintained after 200 cycles. -1 The capacity can still maintain about 100% coulombic efficiency after 200 cycles; -1 Even at high current density, it still provides more than 1000mAh g -1 capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] To more clearly illustrate the technical solutions of the embodiments of this application, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some of the embodiments described in this application. For those skilled in the art, other drawings can be derived from these drawings without inventive effort.

[0026] Figure 1 This is the SEM spectrum of the silicon-aluminum alloy powder prepared in the comparative example;

[0027] Figure 2 This is the SEM spectrum of the silicon-based negative electrode material prepared in Example 1;

[0028] Figure 3 This is the EDS spectrum of the silicon-based negative electrode material prepared in Example 1;

[0029] Figure 4 The charge and discharge performance test chart of lithium battery 1 and lithium battery D1 after 200 cycles;

[0030] Figure 5 This is a rate performance test diagram of lithium battery 1 and lithium battery D1. DETAILED DESCRIPTION

[0031] With reference to the drawings and the embodiments of the present application, the technical solutions in the embodiments of the present application will be clearly and completely described. Obviously, the described embodiments are some of the embodiments of the present application, but not all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort should fall within the scope of the present application.

[0032] In the following description of the embodiments of the present application, the terms "comprising", "containing", "having" and "including" and the like are open-ended terms, i.e., meaning "including, but not limited to".

[0033] In the following description of the embodiments of the present application, the term "and / or" is used to describe the association relationship of the associated objects, which means that there can be three kinds of relationships, for example, A and / or B, which can represent the cases of A alone, B alone and A and B existing at the same time. Wherein A and B can be singular or plural. The character " / " generally represents an "or" relationship between the front and rear associated objects.

[0034] In the following description of the embodiments of the present application, the term "at least one" means one or more, and "multiple" means two or more. "At least one of the following (one)" or similar expressions means any combination of these items, including any combination of single (one) or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can represent a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, wherein a, b, and c can be single or multiple.

[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0036] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of the serial numbers does not mean the order of execution, and some or all steps can be executed in parallel or in sequence, and the execution order of each process should be determined according to its function and inherent logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] Those skilled in the art should understand that the numerical ranges in the embodiments of the present application should be understood as each intermediate value between the upper limit and the lower limit of the range. Each smaller range between any stated value or stated range and any other stated value or intermediate value within the stated range is also included in the present application. The upper limit and the lower limit of these smaller ranges can be independently included or excluded from the range.

[0038] Unless otherwise indicated, the technical / scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which this application belongs. Although this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0039] In a first aspect, the present application provides a silicon-based negative electrode material, comprising a silicon-aluminum alloy substrate and an aluminum fluoride layer coating the silicon-aluminum alloy substrate;

[0040] The silicon-based negative electrode material is prepared by alloying nano-silicon powder and nano-aluminum powder to obtain silicon-aluminum alloy powder, and then performing a fluorination treatment on the silicon-aluminum alloy powder to form an aluminum fluoride layer on the surface.

[0041] This application prepares silicon-aluminum alloy by ball milling, and then fluorinates the silicon-aluminum alloy to form a dense aluminum fluoride film on its surface to obtain a silicon-based negative electrode material, thereby improving the electrical conductivity and stability of the silicon-based negative electrode material. The material has high electrical conductivity, is not easy to pulverize, and has excellent cycle performance and rate performance.

[0042] Specifically, the present application prepares silicon-aluminum alloy by doping aluminum, thereby improving the ductility and conductivity of silicon-based negative electrode materials and greatly reducing the probability of their pulverization and cracking; and the aluminum fluoride coating layer formed by fluorination treatment can not only inhibit the volume expansion of silicon nanoparticles in the silicon-based negative electrode material during the lithium storage process, but also further reduce pulverization and cracking, and improve the utilization rate of active substances.

[0043] In addition, aluminum fluoride formed by fluorination treatment will react with the electrolyte to induce the formation of lithium fluoride, the main substance in the solid electrolyte membrane, thereby regulating the solid electrolyte membrane and effectively solving the performance degradation problem caused by the breakage and reconstruction of the solid electrolyte membrane during battery charging and discharging.

[0044] In a second aspect, the present application provides a method for preparing the above-mentioned silicon-based negative electrode material, comprising:

[0045] S1, take nano-silicon powder and nano-aluminum powder and mix them evenly, and perform ball milling in a ball mill under vacuum to obtain a precursor powder; wherein, the mass ratio of nano-silicon powder to nano-aluminum powder is preferably (1-2):1.

[0046] In this application, the particle size of the nano-silicon powder is preferably 30-50 nm. Wet ball milling is performed using anhydrous ethanol as the milling medium. Ethanol is added to the milling jar until the powder is completely submerged. The preferred ball-to-material ratio is 30:1, the milling speed is 400-600 rpm, and the milling time is 15-20 hours. In this application, zirconia ball milling jars and zirconia ball milling beads are preferably used.

[0047] In the present application, the ball mill jar is vacuumed before ball milling to remove oxygen in the ball mill jar to prevent oxidation of the aluminum powder; preferably, the vacuum degree in the ball mill jar is ≤100Pa.

[0048] S2, the precursor powder is vacuum dried, then heat treated in an inert atmosphere, and cooled to obtain silicon-aluminum alloy powder;

[0049] In the present application, the precursor powder is dried in a vacuum drying device such as a vacuum oven to prevent oxidation of the aluminum powder. The drying temperature is preferably 60° C. and the drying time is 12-24 hours.

[0050] In the present application, the inert atmosphere is preferably an argon atmosphere. In the argon atmosphere, the precursor powder is heated to 650-750° C. and kept warm for 2-3 hours to obtain a silicon-aluminum alloy powder;

[0051] S3, adding the silicon-aluminum alloy powder into a reaction furnace, introducing nitrogen trifluoride gas and reacting at 200-280° C. to obtain a silicon-based negative electrode material. The flow rate of the nitrogen trifluoride gas is 40-60 mL / min, and the reaction time is preferably 1-5 minutes.

[0052] The silicon-based negative electrode material prepared in this application has high electrical conductivity, is not easily pulverized, and has excellent cycle performance and rate performance. It can be used to prepare negative electrode plates for lithium-ion batteries.

[0053] The present application also provides a silicon-based negative electrode plate, which includes the above-mentioned silicon-based negative electrode material. The preparation method of the silicon-based negative electrode plate includes:

[0054] The silicon-based negative electrode material and conductive agent are mixed uniformly to obtain a mixture; the mixture is added to a solution containing an adhesive and mixed uniformly to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of the current collector and dried to obtain a silicon-based negative electrode sheet. The mass ratio of the silicon-based negative electrode material, conductive agent, and adhesive is 8:1:1.

[0055] In the present application, copper foil is selected as the current collector, Surper-p is selected as the conductive agent, and carboxymethyl cellulose is selected as the adhesive; the adhesive solution is an aqueous solution of carboxymethyl cellulose.

[0056] This application also provides a lithium battery whose negative electrode utilizes the silicon-based negative electrode plate of this application, or whose negative electrode comprises the silicon-based negative electrode material of this application. A lithium-ion battery utilizing the silicon-based negative electrode material of this application has high electrical conductivity, long life, and excellent cycle performance and rate capability.

[0057] Illustratively, the lithium battery of the present application uses the silicon-based negative electrode sheet of the present application as the negative electrode; the positive electrode uses a lithium wafer; the solute of the electrolyte is LiPF6, the solvent is a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (EMC) and diethyl carbonate (DEC), and 2% vinylene carbonate (VC) and 10% fluoroethylene carbonate (FEC) are added; the diaphragm uses Celgard2325.

[0058] The present application is further described below through examples.

[0059] Example 1

[0060] S1: Mix 108 mg of nano-silicon powder and 54 mg of nano-aluminum powder, place them evenly in a zirconia ball mill, and add 4.86 g of zirconia ball milling beads. Add 10 ml of anhydrous ethanol dropwise until the powder is completely covered. Evacuate the mill to a vacuum of 100 Pa and then mill at 400 rpm for 20 hours to obtain a precursor powder.

[0061] S2, place the precursor powder in a vacuum drying oven and dry it at 60°C for 12 hours; weigh 200 mg of alloy powder, place it in a porcelain boat, heat it to 700°C in an argon atmosphere and keep it warm for 2 hours, and cool it to room temperature with the furnace to obtain aluminum silicon alloy powder.

[0062] S3, take 60 mg of aluminum-silicon alloy powder and place it in a tube furnace, introduce nitrogen trifluoride gas at a flow rate of 50 mL / min, heat it to 200°C and keep it for 1 minute, and cool it with the furnace to obtain a silicon-based negative electrode material.

[0063] Example 2

[0064] S1: Mix 108 mg of nano-silicon powder and 54 mg of nano-aluminum powder, place them evenly in a zirconia ball mill, and add 4.86 g of zirconia ball milling beads. Add 10 ml of anhydrous ethanol dropwise until the powder is completely covered. Evacuate the mill to a vacuum of 100 Pa and then mill at 400 rpm for 15 hours to obtain a precursor powder.

[0065] S2, place the precursor powder in a vacuum drying oven and dry it at 60°C for 12 hours; weigh 200 mg of alloy powder, place it in a porcelain boat, heat it to 700°C in an argon atmosphere and keep it warm for 2 hours, and cool it to room temperature with the furnace to obtain aluminum silicon alloy powder.

[0066] S3, take 60 mg of aluminum-silicon alloy powder and place it in a tube furnace, introduce nitrogen trifluoride gas at a flow rate of 50 mL / min, heat it to 200°C and keep it for 1 minute, and cool it with the furnace to obtain a silicon-based negative electrode material.

[0067] Example 3

[0068] S1: Mix 108 mg of nano-silicon powder and 54 mg of nano-aluminum powder, place them evenly in a zirconia ball mill, and add 4.86 g of zirconia ball milling beads. Add 10 ml of anhydrous ethanol dropwise until the powder is completely covered. Evacuate the mill to a vacuum of 100 Pa and then mill at 400 rpm for 15 hours to obtain a precursor powder.

[0069] S2, place the precursor powder in a vacuum drying oven and dry it at 60°C for 12 hours; weigh 200 mg of alloy powder, place it in a porcelain boat, heat it to 700°C in an argon atmosphere and keep it warm for 2 hours, and cool it to room temperature with the furnace to obtain aluminum silicon alloy powder.

[0070] S3, take 60 mg of aluminum-silicon alloy powder and place it in a tube furnace, introduce nitrogen trifluoride gas, heat it to 280°C and keep it for 1 minute, and cool it with the furnace to obtain a silicon-based negative electrode material.

[0071] Example 4

[0072] S1: Mix 108 mg of nano-silicon powder and 54 mg of nano-aluminum powder, place them evenly in a zirconia ball mill, and add 4.86 g of zirconia ball milling beads. Add 10 ml of anhydrous ethanol dropwise until the powder is completely covered. Evacuate the mill to a vacuum of 100 Pa and then mill at 400 rpm for 15 hours to obtain a precursor powder.

[0073] S2, place the precursor powder in a vacuum drying oven and dry it at 60°C for 12 hours; weigh 200 mg of alloy powder, place it in a porcelain boat, heat it to 700°C in an argon atmosphere and keep it warm for 2 hours, and cool it to room temperature with the furnace to obtain aluminum silicon alloy powder.

[0074] S3, take 60 mg of aluminum-silicon alloy powder and place it in a tube furnace, introduce nitrogen trifluoride gas, heat it to 280°C and keep it for 5 minutes, and cool it with the furnace to obtain a silicon-based negative electrode material.

[0075] Example 5

[0076] S1: Mix 89 mg of nano-silicon powder and 86 mg of nano-aluminum powder, place them in a zirconia ball mill, and add 5.34 g of zirconia ball milling beads. Add 10 ml of anhydrous ethanol dropwise until the powder is completely covered. Evacuate the mill to a vacuum of 100 Pa and mill at 400 rpm for 15 hours to obtain a precursor powder.

[0077] S2, place the precursor powder in a vacuum drying oven and dry it at 60°C for 12 hours; weigh 200 mg of alloy powder, place it in a porcelain boat, heat it to 700°C in an argon atmosphere and keep it warm for 2 hours, and cool it to room temperature with the furnace to obtain aluminum silicon alloy powder.

[0078] S3, take 60 mg of aluminum-silicon alloy powder and place it in a tube furnace, introduce nitrogen trifluoride gas, heat it to 200°C and keep it for 1 minute, and cool it with the furnace to obtain a silicon-based negative electrode material.

[0079] Comparative Example

[0080] The difference between the comparative example and Example 1 is that step S3 is omitted, that is, the prepared silicon-aluminum alloy powder is not subjected to fluorination treatment, and the rest is the same as Example 1.

[0081] The silicon-based negative electrode material prepared in Example 1 and the silicon-aluminum alloy powder prepared in Comparative Example 1 were subjected to SEM testing to observe their microscopic morphologies. Figure 1 is the SEM spectrum of the silicon aluminum alloy powder prepared in the comparative example, Figure 2 This is the SEM spectrum of the silicon-based negative electrode material prepared in Example 1.

[0082] from Figure 1 It can be seen that in the aluminum-silicon alloy powder obtained after ball milling, aluminum metal and silicon particles are evenly mixed and have a certain spherical morphology. Figure 2 It can be seen that after the silicon-aluminum alloy powder is fluorinated, a dense aluminum fluoride coating layer is generated on the surface of the obtained silicon-based negative electrode material.

[0083] The EDS element distribution test of the silicon-based negative electrode material prepared in Example 1 was performed, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that the three elements of aluminum, silicon and fluorine are evenly distributed in the silicon-based negative electrode material, and the signals are obvious.

[0084] Electrode plates were prepared using the silicon-based negative electrode materials prepared in Examples 1-4 and the silicon-aluminum alloy powder prepared in the comparative example, respectively. The method is as follows: the silicon-based negative electrode material or silicon-aluminum alloy powder and Surper-p are uniformly mixed, and the mixture is added to an aqueous solution of carboxymethyl cellulose and mixed uniformly to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of a copper foil and dried to obtain a silicon-based negative electrode plate. The mass ratio of the silicon-based negative electrode material / silicon-aluminum powder alloy, the conductive agent, and the adhesive is 8:1:1. The electrode plates prepared from the silicon-based negative electrode materials prepared in Examples 1-4 and the silicon-aluminum alloy powder prepared in the comparative example are respectively referred to as negative electrode plates 1-4 and negative electrode plate D1.

[0085] The above-mentioned electrode plates are used as negative electrodes to assemble lithium batteries. The specific methods are as follows:

[0086] The electrode sheets were cut into discs (Φ=12 mm) and the mass loading of active material was 0.4-0.5 mg cm -2 The electrolyte consisted of LiPF6 dissolved in ethylene carbonate (EC), dimethyl carbonate (EMC), and diethyl carbonate (DEC), with 2% vinylene carbonate (VC) and 10% fluoroethylene carbonate (FEC) added. Celgard 2325 was used as the separator, cut into a disc shape (Φ = 16 mm), and a lithium wafer was used as the positive electrode to assemble a lithium battery. The lithium batteries assembled with negative electrode sheets 1-4 and negative electrode sheet D1 are designated as lithium batteries 1-4 and lithium battery D1, respectively.

[0087] The lithium battery 1 containing the silicon-based negative electrode material of Example 1 and the lithium battery D1 containing the silicon-aluminum alloy powder of the comparative example were cycled for 200 cycles to test their charge and discharge performance. The test conditions were: temperature 30°C, current density 0.5A / g, and test voltage window 0.01V to 1.5V. The test results are as follows: Figure 4 shown.

[0088] from Figure 4 It can be seen that the lithium battery 1 using the silicon-based negative electrode material of the present application has a high -1 After 200 cycles at a current density of 1.5 GHz, it can still provide 827 mAh g -1 The capacity of the battery can still maintain about 100% coulombic efficiency after 200 cycles; while the lithium battery D1 of comparative example 1, at 500mAg -1 After 200 cycles at a current density of 1.5, the capacity decreased to 410 mAh g -1 Compared with the comparative example, the charge and discharge performance of the lithium battery containing the silicon-based negative electrode material obtained after fluorination treatment in Example 1 is significantly improved.

[0089] The lithium battery 1 containing the silicon-based negative electrode material of Example 1 and the lithium battery D1 containing the silicon-aluminum alloy powder of the comparative example were subjected to cycle charge and discharge tests to test their rate performance. The test conditions were: temperature 30°C, current density 0.1Ag, and -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 The test voltage window is 0.01V to 1.5V, and the test results are as follows: Figure 5 shown.

[0090] from Figure 5 It can be seen that the lithium battery 1 containing the silicon-based negative electrode material of the present application is -1 Even at high current density, it still provides more than 1000mAh g -1The capacity of lithium battery D1 is 2000mAg -1 The specific capacity is less than 600 mAh g at high current density. -1 This is because the silicon-based negative electrode material of the present application forms a dense aluminum fluoride coating on its surface, which not only inhibits the volume expansion of silicon nanoparticles in the silicon-based negative electrode material during lithium storage, further reducing pulverization and cracking, and improving the utilization rate of active materials; but also aluminum fluoride reacts with the electrolyte to induce the formation of lithium fluoride, the main substance in the solid electrolyte membrane, playing a role in regulating the solid electrolyte membrane and having better rate performance at high current density.

[0091] Corresponding tests were performed on the silicon-based negative electrode materials of Examples 2-5, and their performance was close to that of the silicon-based negative electrode material of Example 1.

[0092] Although this specification has been used to fully describe the present application using general descriptions and specific embodiments, it is obvious to those skilled in the art that modifications or improvements may be made based on the present application. Therefore, such modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in this application.

Claims

1. A silicon-based negative electrode material, characterized in that: It comprises a silicon-aluminum alloy substrate and an aluminum fluoride layer covering the silicon-aluminum alloy substrate; The silicon-based negative electrode material is prepared by alloying nano-silicon powder and nano-aluminum powder to obtain silicon-aluminum alloy powder, and then performing a fluorination treatment on the silicon-aluminum alloy powder to form an aluminum fluoride layer on the surface.

2. The method for preparing the silicon-based negative electrode material according to claim 1, characterized in that: include: S1, taking nano-silicon powder and nano-aluminum powder and mixing them evenly, and ball milling them in a ball mill under vacuum to obtain a precursor powder; S2, the precursor powder is vacuum dried, then heat treated in an inert atmosphere, and cooled to obtain silicon-aluminum alloy powder; S3, adding the silicon-aluminum alloy powder into a reaction furnace, introducing nitrogen trifluoride gas at 200-280° C. to react, thereby obtaining a silicon-based negative electrode material.

3. The preparation method according to claim 2, characterized in that The ball milling is wet ball milling, and the ball milling medium is anhydrous ethanol.

4. The preparation method according to claim 3, characterized in that The ball-to-material ratio of the ball mill is 30:1, the rotation speed is 400-600 r / min, and the time is 15-20 hours.

5. The preparation method according to claim 3, characterized in that The vacuum degree in the ball mill is ≤100Pa.

6. The preparation method according to claim 2, characterized in that The heat treatment specifically comprises: heating to 650-750° C. in an inert atmosphere and keeping the temperature for 2-3 hours.

7. The preparation method according to claim 2, characterized in that In step S3, the flow rate of nitrogen trifluoride gas is 40-60 mL / min, and the reaction time is 1-5 min.

8. The preparation method according to claim 2, characterized in that The mass ratio of the nano silicon powder to the nano aluminum powder is (1-2):

1.

9. A silicon-based negative electrode plate, characterized in that: It comprises the silicon-based negative electrode material according to claim 1.

10. A lithium ion battery, characterized in that: The negative electrode is the silicon-based negative electrode plate as claimed in claim 9.